2015
DOI: 10.1007/s10157-015-1082-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel prediction model of renal function after nephrectomy from automated renal volumetry with preoperative multidetector computed tomography (MDCT)

Abstract: Combining MDCT renal volumetry and clinical indices might yield an important tool for predicting postoperative renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Isotani et al demonstrated a significant correlation between percent eGFR alteration and percent renal parenchymal volume preservation in 60 cases treated with RN using SYN-APSE VINCENT. 14 Although there was no significant association between renal parenchymal change and post-PN renal global function, our study is the first to demonstrate the significant post-PN compensatory hypertrophy in contralateral kidney using sophisticated film technology, SYNAPSE VINCENT. Outside of the urological field, the usefulness of SYNAPSE VINCENT as the image-supported navigation has also been reported in thoracic and hepatic surgical fields.…”
Section: Renal Global Function Is the Summation Of Ipsilateral Renal mentioning
confidence: 49%
“…Isotani et al demonstrated a significant correlation between percent eGFR alteration and percent renal parenchymal volume preservation in 60 cases treated with RN using SYN-APSE VINCENT. 14 Although there was no significant association between renal parenchymal change and post-PN renal global function, our study is the first to demonstrate the significant post-PN compensatory hypertrophy in contralateral kidney using sophisticated film technology, SYNAPSE VINCENT. Outside of the urological field, the usefulness of SYNAPSE VINCENT as the image-supported navigation has also been reported in thoracic and hepatic surgical fields.…”
Section: Renal Global Function Is the Summation Of Ipsilateral Renal mentioning
confidence: 49%
“…In this study, sophisticated film technology, Synapse Vincent, was used for the soft volumetric analysis. The employment of Synapse Vincent demonstrated that it had a significant correlation between percent eGFR alteration and percent RPV preservation in 60 cases treated with RN [22]. The finding in this study that postoperative contralateral RPV was significantly larger than preoperative RPV suggests that compensatory renal hypertrophy (CRH) of the contralateral side likely occurs 6 month postoperatively.…”
Section: Discussionmentioning
confidence: 65%
“…In these patients, preoperative CT based RPV measurements were found to be independently associated with the development of CKD after surgery. Isotani et al reported similar results in their cohort of 60 patients undergoing radical nephrectomy who underwent renal volumetry using CT and GFR measurement by MDRD equation (r=0.54) (20). Besides Kuru et al, only three more studies have correlated MRI renal volumetry with renal function/GFR for patients undergoing nephrectomy ( Table-2) (21-23).…”
Section: Discussionmentioning
confidence: 77%